2021
DOI: 10.1136/bmjopen-2021-058885
|View full text |Cite
|
Sign up to set email alerts
|

Striving for autonomy in everyday diabetes self-management—qualitative exploration via grounded theory approach

Abstract: ObjectivesThe rapid worldwide increase in the incidence of diabetes significantly influences the lives of individuals, families and communities. Diabetes self-management requires personal autonomy and the presence of a supportive social environment. These attributes can considerably ameliorate the outcomes of the chronic condition. However, little is known about individual variations in overcoming the illness-related challenges and in the achievement of autonomy in daily activities. This paper seeks to bridge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Autonomous motivation is important in adopting and maintaining DSM practices that improve glycemic control [ 34 , 35 ]. DSM requires continual improvement of disease-related knowledge in patients as well as maintaining engagement, skills, and self-efficacy [ 36 ]. DSM was identified as the principal construct to assess for this domain.…”
Section: Resultsmentioning
confidence: 99%
“…Autonomous motivation is important in adopting and maintaining DSM practices that improve glycemic control [ 34 , 35 ]. DSM requires continual improvement of disease-related knowledge in patients as well as maintaining engagement, skills, and self-efficacy [ 36 ]. DSM was identified as the principal construct to assess for this domain.…”
Section: Resultsmentioning
confidence: 99%
“…Psychosocial interventions targeting self-efficacy should be an inseparable component of diabetes control treatment regimens. Although several past and recent studies based on autonomy motivation and support have shown the importance of promoting self-efficacy for the long-term maintenance of diabetes management (Anderson et al, 2009;Chen et al, 2022;Funnell et al, 2007;Lee et al, 2019;Sallay et al, 2021;Tang et al, 2005), few studies have explored the nuances of phase-specific self-efficacy and their influence on self-care behaviors among the T2D population. Recently, Ranjbaran et al (2020) reported a significant association between task self-efficacy, maintenance self-efficacy, and medication adherence among individuals with T2D, reflecting the need for more studies to examine the various facets of self-efficacy and predict different self-care activities involved in diabetes management.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is well-suited to provide data about social and medical determinants of well-being and provides a multitude of variables relevant to the presented research questions. The DEAS is an ongoing survey with currently six waves (1996–2017) and several shorter surveys during the COVID-19 pandemic (2020–2022) 37 . In accordance with the German Research Foundation (Deutsche Forschungsgemeinschaft, DFG) and the Institute for Applied Social Science (INFAS), no ethics approval was needed for the study as data were collected under pseudonyms and voluntarily, and the study was deemed low-risk, as no work on patients was included.…”
Section: Methodsmentioning
confidence: 99%
“…In a second step, we aimed to understand the particular characteristics of social exclusion in people with diabetes. For this purpose, we determined how social exclusion in people with diabetes is associated with various medical and psychosocial cofactors that are known to be relevant for social exclusion 10 , 11 , 22 : sex, higher BMI/obesity 10 , 33 , 34 , socioeconomic status 35 , multimorbidity 36 , depression 10 , 22 , 23 , loneliness 28 , self-esteem and self-efficacy 22 , 23 , physical function 10 , and autonomy 37 . Finally, we used longitudinal data to explore the onset of social exclusion in people with diabetes, and whether diabetes itself can be considered a risk factor for social exclusion.…”
Section: Introductionmentioning
confidence: 99%